2015
DOI: 10.1007/s00261-015-0581-y
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of abdominal findings in Crimean-Congo hemorrhagic fever

Abstract: Our study is the first comprehensive study on abdominal MDCT findings of CCHF. We detected a strong relationship between patients' platelet count and abdominal free liquid. Therefore, it should be kept in mind that abdominal free fluid can be among clinical manifestations in patients with platelet counts ≤50000 and that this manifestation can become aggravated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
0
12
2
3
Order By: Relevance
“…In the same study, the laboratory findings and CT outcomes were compared, and the presence of abdominal free fluid was statistically significant in patients with a platelet count lower than 50,000. As compared with the reports in the literature [22,23], the incidence of hepatomegaly was lower (16.7%) in the present study, and the incidence of splenomegaly was higher (27.1%). In the present study, abdominal free fluid was found in only one patient.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…In the same study, the laboratory findings and CT outcomes were compared, and the presence of abdominal free fluid was statistically significant in patients with a platelet count lower than 50,000. As compared with the reports in the literature [22,23], the incidence of hepatomegaly was lower (16.7%) in the present study, and the incidence of splenomegaly was higher (27.1%). In the present study, abdominal free fluid was found in only one patient.…”
Section: Discussioncontrasting
confidence: 63%
“…In the present study, abdominal free fluid was found in only one patient. Thus, the incidence was much lower (2.1%) than that reported in the earlier studies [22,23]. In the study by Ziraman et al, the radiological investigations were performed a mean of 7.8 days after the onset of symptoms, whereas they were performed a mean of 3.6 days after symptom onset in our study.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…There have been many studies performed on CCHF in the literature. However, the number of studies related to pulmonary imaging in CCHF is very rare and limited despite the increasing number of cases in the world and in our country [1][2][3][4]. On the other hand, we have a distinct advantage of studying the CCHF patients due to the increase in the frequency of the disease in our region.…”
Section: Introductionmentioning
confidence: 99%
“…However, ecchymosis, petechia, vaginal bleeding, and epistaxis can also be observed. In addition, intracranial bleeding, gastrointestinal bleeding, and alveolar hemorrhage that are life-threatening and often responsible for mortality can be observed as well [1][2][3][4]. The geographical location, exposure to animals with ticks, and contact with suspicious infected blood and blood products in the patients' history are helpful in diagnosis.…”
Section: Introductionmentioning
confidence: 99%